Leitura e produção de histórias em quadrinhos digitais : uma proposta de uso do smartphone - Valadares, Nice Vânia Machado Rodrigues (2019)
The presence of the new technologies of communication and information in our lives gave rise to a new profile of reader and producer of texts, adapted to the movement of the screens, to the speed of the images, immersed in synchronous and asynchronous relations of communication, a dynamic individual, that interacts at all times, with their peers and with the electronic equipment. This new scenario requires the individuals' skills needed to use information strategically, critically and dynamically. These changes enable individuals to immerse themselves in multimodalities and multimedia resources. In view of the above, this research is developed from a multimodality perspective, implemented in a class of twenty-nine students, from the 6th grade of Elementary School of a school in the State of Sergipe. The base of this TCW is the textual genre: Comic Books, which will be used as a medium, along with the cellular, in order to develop as digital final product, which will be organized in videos, and published in a Blog, called "Digital Comic Stories." This TCW is divided into five chapters: the first (relationship between technology and education), the second (textual genres and comics), the third (methodological process used for the construction and development of the research), and the fourth (presentation and analysis of the data collected). It aims to verify the contribution of the Comic Stories in the improvement of reading, writing and critical skills, from the implementation of a workshop with eight moments, based on the Cosson (2011) model, consisting of four stages: motivation, introduction , reading and interpretation, having to add two more: reformulation, production and publication. As for the methodology of the study, the research is based on the qualitative and field bibliographical. The theoretical course of this TCF is based on the contribution of Jenkins (2009), who approaches the convergence of the media, Santaella (2013), with the theory of ubiquity; Marcuschi (2008), Dolz (2004) e Dolz e Schneuwly (1999) that deal with the textual genres; and about the comics, the conceptions of Santos and Vergueiro (2012), Eisner (1989) and Santos (2003) are approached. It is hoped, therefore, to improve the students' reading and writing process, from the implementation of multimodality, by instigating the student to be able to criticize, select, identify, produce multisemiotic and multimodal texts, which in turn are multiplied in meanings.